Financial prudence and time mastery: lived experiences of urban low-income working mothers in Malaysia - Baharuddin, Najwa; Burhan, Nik Ahmad Sufian; Hussin, Ruhaya; Mohd. Janis, Fadzilla Hernani; Sabri, Mohd. Fazli (Malaysian Consumer and Family Economics Association (MACFEA), 2025)
Urban low-income working mothers in Malaysia face persistent challenges in balancing paid work and caregiving within limited financial and temporal resources. This study explores their lived experiences and the strategies they employ to navigate these constraints. Eight participants from Klang Valley took part in an Interpretative Phenomenological Analysis study involving seven-day diaries (June–July 2021) and subsequent in-depth interviews (November–December 2021). The findings are interpretive and aim to illuminate lived experiences rather than generalise prevalence. Participants demonstrated financial prudence and mindful time management skills to cope with caregiving responsibilities and employment demands. While financial literacy supported daily budgeting and savings, it was insufficient to ensure long-term stability, particularly during unexpected events such as the COVID-19 pandemic. Time management appeared as equally important, with participants developing structured routines to reduce stress and maximise limited resources. They emphasise the interdependence of financial and temporal resources and the importance of tailored support programs that include both financial and time management training. These findings contribute to family economics by demonstrating that the resource-management and coping strategies employed by low-income working mothers can inform more inclusive intervention and policy design.